Women and media: A critical introduction - Byerly, Carolyn M.; Ross, Karen (John Wiley & Sons, 2008)
Women and Media is a thoughtful cross-cultural examination of the ways in which women have worked inside and outside mainstream media organizations since the 1970s. Rooted in a series of interviews with women media workers and activists collected specifically for this book, the text provides an original insight into women’s experiences. Explains the ways that women have organized their internal and external campaigns to improve media content (or working conditions) for women, and established womenowned media to gain a public voice. Identifies key issues and developments in feminist media critiques and interventions over the last 30 years, as these relate to production, representation and consumption. Functions as both a research case study and a teaching text.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; cinéma; communication; discipline; histoire et politique; médias; projet charge mentale; périodes historiques; ressource en ligne; thématiques; travail

Book Review: Making Space for Indigenous Feminism - Charron, Nadine (Gender and Development, 2008)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; critique de livre; féminisme autochtone; histoire et politique; militance; pol4105; pol5185; premier cycle; périodes historiques; régions géographiques; thématiques

Globalization as Racialized, Sexualized Violence THE CASE OF INDIGENOUS WOMEN - Kuokkanen, Rauna (International Feminist Journal of Politics, 2008)
In my article, I suggest that indigenous women are among the hardest hit by economic globalization – the expansion of markets, trade liberalization and cheapening of labour – and that globalization represents a multifaceted violence against indigenous women. I consider this with the help of two examples. First, I discuss the largely ignored case of missing and murdered Aboriginal women in Canada and how the interlocking systems of oppression (colonization, patriarchy and capitalism) are further intensified by globalization. Second, I examine the death of a Hopi woman, Private Piestewa, in the context of militarization, history of colonization and globalization. I analyse these examples in an intersectional framework that reveals the links between colonization, patriarchy and capitalism all of which inform the current processes of globalization.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; armée états-unienne; canada; capitalisme; cours; discipline; féminicide; globalisation; histoire et politique; intersectionnalité; militarisation; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis

Genre et développement : Enjeux et luttes des femmes du Tiers-monde dans Introduction au développement international: approches, acteurs et enjeux - Martinez, A.; Beaudet, Pierre; Haslam, Paul Alexander; Schafer, Jessica (Introduction au développement international: approches, acteurs et enjeux, 2008)
Section: x, 507 pages : illustrations, cartes ; 24 cm
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; développement; féminisme décolonial; histoire et politique; pol4022; premier cycle; privilèges; périodes historiques; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

L’impact des violences structurelle et conjugale en contexte migratoire: Perceptions d’intervenants pour le contrer - Rojas-Viger, Celia (Nouvelles pratiques sociales, 2008)
Résumé Le Canada et le Québec, sociétés pluriethniques, possèdent des politiques et des programmes de promotion et de prévention pour contrer les violences faites aux femmes, mais reconnaissent que le défi est de taille dans le contexte migratoire. Les immigrantes, confrontées à la violence conjugale, ne disposent souvent pas d’accessibilité culturelle aux services sociaux et de santé ou n’obtiennent pas de réponse adéquate à leurs besoins. Toutefois, certains organismes ont des projets pour leur venir en aide mais ils ne sont pas systématiques. L’article présente les résultats d’une recherche exploratoire, avec approche ethnologique, qui documente la perception de 10 intervenants d’organismes communautaires et institutionnels concernant leurs activités dans le domaine et leur préoccupation pour la promotion et la prévention primaire, même si leurs pratiques concrètes sont surtout centrées sur la prévention secondaire. Maints empêchements les limitent, mais leurs perceptions des réponses promotionnelles et préventives mettent en lumière l’impact de la violence structurelle et de la violence conjugale et orientent les perspectives de renouvellement des pratiques d’intervention sociosanitaire en matière de violence conjugale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; médecine; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; systèmes d'oppressions; thématiques; trs3500; violence systémique; violences; violences conjugales

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques